Safety and Feasibility of Cervical and Thoracic Transcutaneous Spinal Cord Stimulation to Improve Hand Motor Function in Children With Chronic Spinal Cord Injury - Singh, Goutam; Keller, Anastasia; Lucas, Kathryn; Borders, Catherine; Stout, Danielle; King, Molly; Parikh, Parth; Stepp, Nicole; Ugiliweneza, Beatrice; D’Amico, Jessica M.; Gerasimenko, Yury; Behrman, Andrea L. (Neuromodulation (Malden, Mass.), 2024)
In adults with cervical spinal cord injury (SCI), transcutaneous spinal stimulation (scTS) has improved upper extremity strength and control. This novel noninvasive neurotherapeutic approach combined with training may modulate the inherent developmental plasticity of children with SCI, providing even greater improvements than training or stimulation alone. Because children with SCI represent a vulnerable population, we first must establish the safety and feasibility of any potential novel therapeutic approach. The objectives of this pilot study were to determine the safety, feasibility, and proof of principle of cervical and thoracic scTS for short-term effect on upper extremity strength in children with SCI. In this nonrandomized, within-subject repeated measure design, seven participants with chronic cervical SCI performed upper extremity motor tasks without and with cervical (C3–C4 and C6–C7) and thoracic (T10–T11) site scTS. Safety and feasibility of using cervical and thoracic sites scTS were determined by the frequency count of anticipated and unanticipated risks (eg, pain, numbness). Proof-of-principle concept was tested via change in force production during hand motor tasks. All seven participants tolerated cervical and thoracic scTS across the three days, with a wide range of stimulation intensities (cervical sites = 20–70 mA and thoracic site = 25–190 mA). Skin redness at the stimulation sites was observed in four of 21 assessments (19%) and dissipated in a few hours. No episode of autonomic dysreflexia was observed or reported. Hemodynamic parameters (systolic blood pressure and heart rate) remained within stable limits (p > 0.05) throughout the assessment time points at baseline, with scTS, and after the experiment. Hand-grip and wrist-extension strength increased (p < 0.05) with scTS. We indicated that short-term application of scTS via two cervical and one thoracic site is safe and feasible in children with SCI and resulted in immediate improvements in hand-grip and wrist-extension strength in the presence of scTS. The Clinicaltrials.gov registration number for the study is NCT04032990.